Роман Доріт Лінке „По той бік блакитної межі”: екскурс в минуле „оссі” для сучасних підлітків - Isapchuk, Yulia (Питання літературознавства, 2021)
The article analyses the debut historical juvenile novel by the German writer Dorit Linke (b. 1971) „Beyond the Blue Border” („Jenseits der blauen Grenze”, 2014) in the aspect of the literary, historical and pedagogical potential of the text. The main events take place in the Baltic Sea in August 1989 when youths tried to escape from Rostock to West Germany with flashbacks into their life in the GDR. The connection between the periods of the late 1960s and 1980s is emphasized. It was a time of formation or changing the worldview of the main novel’s characters, which belong to three different generations: 1933 (grandfather), 1968 (parents) and 1989 (teenagers). The title of the book points to a kind of marine locus, representing the key stereotypes about the element of water and the inner state of the heroes. The sea is regarded as a constitutive topos, which not only performs the traditional background function of nature but also turns into an artistic image of a literary text. The narrative from the perspective of a teenage girl makes it possible to explain better to the reader of the appropriate age the motives of the incredible act of their peers and helps to get insight into the everyday life of the „Ossi” (residents of East Germany) in contrast to the „Wessi” (West Germans). In this way, the modern German historical juvenile literature demonstrates the relevance for its recipients, performing the cognitive and didactic functions without aggressive interference in the minds of adolescents.
Keywords: Доріт Лінке, німецька історична ювенальна література, НДР, „оссі”, Балтійське море, межа.